Management of market surveillance authorities for construction products - Kouros, Kyriacos I.; Chrysostomou, Christis (My University, 2020)
Background: The Construction Products Regulation (CPR) entered into full force in the European Union (EU) on 1 July 2013 aiming to improve the free movement of construction products. Several EU Commission Reports acknowledge as one of the main shortcomings, the less than active role of Member States in market surveillance and suggest examining and implementing methods for more efficient prioritisation and organisation of market surveillance activities. Objective: The purpose of the paper is to investigate management elements of the Market Surveillance Authorities (MSAs) for construction products in the EU. To this end, and to collect information on the current level of effectiveness of the organisational approach of the MSAs, it is imperative to collect information on the main relevant management activities of the MSAs, i.e. strategic analysis, risk assessment and performance measurement. Methods: The paper presents background information on the level of market surveillance in the EU. In order to provide further insight, a survey was carried out to collect information and views from representatives of the Member States’ MSAs of construction products participating in the EU committee “Administrative Cooperation Group for the Construction Products Regulation” (AdCo-CPR). Results: Through the findings of investigating management perspectives of the MSAs, it can be concluded that currently, market surveillance of construction products in the Member States markets is limited, and MSAs should consider implementing a quality management system to improve the effectiveness of market surveillance activities as well as to create public value. Conclusion: The findings also suggest that further investigation is needed to be related to strategy, risk and performance management of the MSAs in order to enhance performance and effectiveness.
Keywords: Construction products; European Union; ISO 9001; Market surveillance; Public service; Quality management system